Synthesis of Natural Products, Carbocycles, and Heterocycles by Hauser–Kraus Annulation - Sankara, Chenikkayala Siva; Gaikwad, Shweta Prakash; Namboothiri, Irishi N. N. (Synlett, 2023)
In this Account, we summarize recent developments in Hauser–Kraus (H–K) annulation with respect to syntheses of natural products and other functionalized, fused, or spiro carbocycles and heterocycles. Although the classical H–K annulation occurs between a 1,4-dipolar synthon (a 3-nucleophilic phthalide), and a 1,2-dipolar synthon (a Michael acceptor), alternative modes of annulation, such as [4+4] and [4+1], as well as other reactivities of 3-nucleophilic phthalides that have been reported in recent years, are also covered in this account.1 Introduction2 Hauser–Kraus Annulation in Total Syntheses3 Hauser–Kraus Annulation Methodologies3.1 [4+2] Annulation3.2 [4+4] Annulation Followed by Rearrangement3.3 Michael Addition Followed by E2 Elimination4 Miscellaneous Reactions5 Conclusions
Keywords: phthalides; Hauser–Kraus annulation; natural products; Dieckmann cyclization; spiro compounds; cascade reactions